The Effect of Usability and Information Quality on Decision Support Information System (DSS) - Atta, Mohammed Thamir (OMICS International, 2017)
Decision-making is complex process that involves people and information system. A Decision Support Systems (DSS) is a set of specific class of computerized information systems that support decision making activities of businesses and organizations. There are certain factors that affect the performance of DSS such as information quality and usability of these systems. This study aims to introduce the concept of usability and information quality in general and examining their effects on the DSS. The study found that both usability and information quality have strong effect on the output of any information system and in particular DSS. The study recommended that the developers of information systems must pay high attention to develop the content provided by IS before process them by DSS as well as they ensure DSS is easy to use and get required information to support decision making process, for example the developers should focus on easy navigation through the system, good interface and reaching information in proper time.